Transmembrane Adaptor Proteins in the High-Affinity IgE Receptor Signaling - Draber, Petr; Halova, Ivana; Levi-Schaffer, Francesca; Draberova, Lubica (Frontiers in Immunology, 2012)
Aggregation of the high-affinity IgE receptor (FcεRI) initiates a cascade of signaling events leading to release of preformed inflammatory and allergy mediators and de novo synthesis and secretion of cytokines and other compounds. The first biochemically well defined step of this signaling cascade is tyrosine phosphorylation of the FcεRI subunits by Src family kinase Lyn, followed by recruitment and activation of Syk kinase. Activity of Syk is decisive for the formation of multicomponent signaling assemblies, the signalosomes, in the vicinity of the receptors. Formation of the signalosomes is dependent on the presence of transmembrane adaptor proteins (TRAPs). These proteins are characterized by a short extracellular domain, a single transmembrane domain and a cytoplasmic tail with various motifs serving as anchors for cytoplasmic signaling molecules. In mast cells five TRAPs have been identified (LAT, NTAL, LAX, PAG and GAPT); engagement of four of them (LAT, NTAL, LAX and PAG) in FcεRI signaling has been documented. Here we discuss recent progress in the understanding of how TRAPs affect FcεRI-mediated mast cell signaling. The combined data indicate that individual TRAPs have irreplaceable roles in important signaling events such as calcium response, degranulation, cytokines production and chemotaxis.